2015
DOI: 10.18488/journal.68/2015.2.3/68.3.100.113
|View full text |Cite
|
Sign up to set email alerts
|

Genotype X Environment Interaction and Stability Analysis for Yield and Yield Related Traits of Desi-Type Chickpea (Cicer Arietinum L.) In Ethiopia

Abstract: Chickpea is the major pulses grown in Ethiopia DZ-2012-CK-0040, DZ-2012-CK-0036 and DZ-2012-CK-0040, DZ-2012 and variety Natoli were recommended as specifically adapted to sites Akaki, Chefe Donsa, Debre Zeit, Dembia and Haramaya respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
4
7
0
Order By: Relevance
“…The predominance of linear component would help in predicting the performance of genotypes across environments. This also suggested that prediction for these attributes would be perfect, these results supporting the earlier findings of Hasan et al, (2008), Segherloo et al, (2008), Alwawi, Choumane (2010) and Tilahun et al, (2015). The genotypes had regression coefficient lesser than unity coupled with mean values less to grand mean revealed that above average stability of genotypes.…”
Section: Stability Analysissupporting
confidence: 86%
“…The predominance of linear component would help in predicting the performance of genotypes across environments. This also suggested that prediction for these attributes would be perfect, these results supporting the earlier findings of Hasan et al, (2008), Segherloo et al, (2008), Alwawi, Choumane (2010) and Tilahun et al, (2015). The genotypes had regression coefficient lesser than unity coupled with mean values less to grand mean revealed that above average stability of genotypes.…”
Section: Stability Analysissupporting
confidence: 86%
“…These results were in general agreement with the findings reported by Johnson et al (2018), Sharma and Johnson (2017), Rao (2011), Shivani and Sreelakshmi (2015), Tilahun et al (2015), Johnson et al (2015), Yadav et al (2010), Yadav et al (2014), Rao and Rao (2014) and Johnson et al (2016).…”
supporting
confidence: 92%
“…The Chickpea crop shows differential performance when grown under different environments after the harvest of rice. Environmental factors such as soil moisture, sowing time, fertility and temperature and day length have strong influence during various stages of plant growth (Tilahun et al, 2015). The environment is changing day-by-day and this implies that it is necessary to evaluate crop genotypes at different environments or agro-climatic zones to assess their real performances.…”
mentioning
confidence: 99%
“…Each of these genotypes yielded 0.5 t ha -1 over the average on the respective location. These genotypes also yielded the highest in the associated environments in the GGE bi-plots (Figures 2 and 3 Kan et al (2010) on the stable genotypes yielding higher than the general average, and Tilahun et al (2015) for genotypic performance based on average across the locations involved. …”
Section: Cifwn = Chickpea International Fusarium Wilt Nurserymentioning
confidence: 84%
“…Graphical tools for identification of mega-environments and specifically adapted genotypes are presented in Yan et al, (2000) and Yan (2011). In neighboring Iranian environments, an analysis of genotype by environment data was carried out to examine the nature of genotype by environmental interaction in chickpea by Farshadfar et al, (2011).While several studies to evaluate GEI in chickpea have been reported for environments in many countries (Bakhsh et al, 2011;Singh et al, 1990;Bozoglu & Gulumser, 2000;Farshadfar et al, 2011;Imtiaz et al, 2013;Tilahun et al, 2015), but such an evaluation is not available for chickpea growing environments in Afghanistan.…”
mentioning
confidence: 99%